PENGARUH SIZE, PROFITABILITAS, LEVERAGE DAN UMUR PERUSAHAAN TERHADAP PENGUNGKAPAN TANGGUNGJAWAB SOSIAL PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2014-2018) - Ike Nur Irianti; Paulus Kombo Allo Layuk; Hastutie Noor Andrianti (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This research aims to obtain empirical evidence on the analysis of factors influencing The disclosure of Corporate social responsibility in manufacturing companies in Indonesia. Factors used include Size, Profitability, Leverage, and age of the company. Measurement of the corporate social responsibility disclosure Using the Global REPORTING Initiative (GRI). There are 79 items to detect the level of disclosure of corporate social responsibility. The population of this research is all the financial data of manufacturing companies listed on IDX period 2014-2018. The sample determination method used in this study is the purposive sampling method. The samples used in this research are all manufacturing companies that publish annual and financial reports during the observation period. Total sample used in this study as much as 40 companies. The data used is secondary data from IDX. The analytical techniques used are multiple linear regression analyses.The results of this study showed that the company size affects the disclosure of corporate social responsibility, while profitability, leverage, and the company's age do not affect the disclosure ofcorporate social responsibility.